1986
DOI: 10.1111/j.1471-0307.1986.tb02356.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient content of milk and milk products: vitamins of the B complex and vitamin C in retail market milk and milk products

Abstract: A survey was undertaken to update and extend information on the water‐soluble vitamin content of milk and milk products on retail sale. The results are discussed in relation to previously published data. Apart from vitamin C the levels of vitamins in retail pasteurized cows' milk were very similar to those found in milk from the processing dairy. Levels of total vitamin C and folic acid in UHT full cream milk were negligible; vitamin B6 and vitamin B12 were respectively 73 and 56% of the levels in pasteurized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 4 publications
3
23
0
Order By: Relevance
“…Generally, the ascorbic acid values reported in the milk of cows in the present experiment were low and were only about one-tenth of the ascorbic acid found in milk of the sow (Wegger and Palludan, 1982). The values for ascorbic acid concentration in cow milk obtained in the present experiment were similar to those reported by Scott and Bishop (1986).…”
Section: Introductionsupporting
confidence: 91%
“…Generally, the ascorbic acid values reported in the milk of cows in the present experiment were low and were only about one-tenth of the ascorbic acid found in milk of the sow (Wegger and Palludan, 1982). The values for ascorbic acid concentration in cow milk obtained in the present experiment were similar to those reported by Scott and Bishop (1986).…”
Section: Introductionsupporting
confidence: 91%
“…Scott and Bishop (1986) observed almost 10% more riboflavin in summer milk than in winter milk, from both cows and goats. Milks from other species are often good sources of vitamin B2• Abd El-Gawad et a/.…”
Section: Riboflavin In Milk and Milk Productsmentioning
confidence: 87%
“…Sheep's milk contains about twice as much thiamin as cow's milk (Scott and Bishop, 1986). Milk from the two main breeds of Saudi Arabian goats had a thiamin content of 47 and 30 J.lg/100 g, respectively (Sawaya et a/., 1984).…”
Section: Thiamin In Milk and Milk Productsmentioning
confidence: 99%
“…These have included studies on bulk liquid milk (Scott et a1 1984;Florence et a1 1985); baby milk formula (Scott and Bishop 1985); retail milk and milk products (Scott and Bishop 1986); and the concluding studies reported in this and the preceding paper (Scott and Bishop 1988) on cheeses, creams, ice creams and milk shakes.…”
Section: Generalmentioning
confidence: 99%